(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article is devoted to the issues of interactive learning of children of primary school age. Interactive methods and technologies are proposed for use in lessons in primary school, taking into account the psychological and pedagogical characteristics of primary school age.